Correction: Kwiatosz-Muc et al. Personality Traits and the Sense of Self-Efficacy among Nurse Anaesthetists. Multi-Centre Questionnaire Survey. Int. J. Environ. Res. Public Health 2021, 18, 9381 - Magdalena Kwiatosz-Muc (MDPI AG, 2021)
There was an error in the original article [...]